Assessing pension system outcomes in Brazil: a stock-flow consistent analysis - Nogueira Silva, Daniel; Morrone, Henrique; Kappes, Sylvio (Brazilian Keynesian Review, 2022)
The pension system serves as an important instrument to provide income for individuals who are incapacitated for work or achieve old age. Recently, Pension Systems worldwide have faced financial and actuarial difficulties, casting doubts about their sustainability. Arguably, the main reasons for the systemic unbalance are the ageing population and the structure of benefits. The present article investigates the impacts of these two variables by means of simulation exercises. Specifically, this paper aims to analyze how a rise in formality and an increase in labor productivity affect the results for the Brazilian Pension System (deficit or surplus), the participation of the benefits in total GDP and economic growth, based on a stock-flow consistent model (SFC). The results reveal that increasing formalization (i.e, rising the number of taxpayers) reduces the pension system deficit and boost economic growth. But the system deficit persists somewhat. Allowing for productivity growth improves the results.